Level of Awareness, Interest Between Gender and Perception of Students Towards STEM - MASRAN, NUR LIYANA; Sulaiman, Adawiah; Masek, Alias (Research and Innovation in Technical and Vocational Education and Training, 2022)
The goals of this study are to investigate lower secondary student progress in their awareness, perceptions, and interests towards Science, Technology, Engineering, and Mathematics (STEM) within the context of a professional development program. Currently, less than 20% of students take STEM subjects compared to the target of 60%. Most STEM based study programs at Public Universities have been unpopular. Parents are less interested and do not encourage their children to study in STEM education. Students are also less interested in STEM education because they consider the subject difficult; the learning is less interesting and boring. Furthermore, they feel that another STEM graduate is able to get good jobs and career prospects. Previous research also reported that students 'attitudes and appreciation towards science were high while students' self -confidence in science was low. Although many students have positive attitudes and interests towards science and mathematics. A case study was conducted to 61 students (23 male: 38 female) in one of the schools in Johor using questionnaire. This research proved that positive awareness of students towards STEM (M=3.93, SD=0.68), positive interest of male (M=3.46, SD=0.78), positive interest of female (M= 3.92, SD=0.68) and perception (M=3.85, SD=0.68) on STEM. The results point to the need to help teacher in designing certain aspects of STEM lesson plans including program or webinar meaningfully into the lesson content.